eDNA analysis reveals high invasion risks in nature reserves in Guangdong Province, China - Wei, Yufeng; Wu, Chunyan; Zhang, Saisai; Xia, Zhiqiang; Gao, Yangchun (Frontiers in Marine Science, 2024)
Introduction Invasive species can cause ecological and economic damage in various areas, including nature reserves. The invasion risks of aquatic invasive vertebrates in nature reserves, however, remain unclear since this group often hides under the water and is frequently neglected in ecological surveys based on traditional methods. Methods Environmental DNA (eDNA) provides a promising alternative way to conduct biodiversity surveys in aquatic ecosystems. Here, we collected aquatic eDNA samples from eight nature reserves in Guangdong Province, China to mainly investigate the diversity of aquatic invasive vertebrates and inform their invasion risks in these nature reserves. Results and discussion We detected a total of 104 aquatic vertebrate species belonging to three classes (Actinopteri, Amphibia and Reptilia), 12 orders, 32 families, and 71 genera, among which nine were invasive species (8.65% of all aquatic vertebrates detected), i.e., Coptodon zillii, Sarotherodon galilaeus, Oreochromis niloticus, Oreochromis tanganicae, Gambusia affinis, Clarias gariepinus, Chelydra serpentina, Trachemys scripta elegans, and Rana catesbeiana. Surprisingly, 55.56% of these aquatic invasive vertebrates (i.e., five species) were found in at least 75.00% samples, and both C. zillii and S. galilaeus were detected in all samples (100%), suggesting that most invasive species were widely distributed in these nature reserves. In addition, all aquatic invasive vertebrate species ranked very high (top 66 of aquatic vertebrates detected) regarding their relative abundance of sequences, and three of the top 10 species with the highest number of sequences were invasive species (i.e., C. zillii, S. galilaeus, and O. niloticus), suggesting high population size of these invasive vertebrates. Moreover, we also detected 16 endangered/threatened species (15.38% of all vertebrates detected), which demonstrated notable overlaps of geographic distribution with invasive species. The reality of high abundance, wide geographical distribution and overlaps with the endangered/threatened species indicated considerable risks of aquatic invasive vertebrates in nature reserves in Guangdong Province, which calls for urgent needs for effective management. Our study would provide fundamental insights for the formulation of effective management measures to reduce losses caused by invasive species and promote the protection of endangered/threatened species in nature reserves.